Acid Pretreatment to Enhance Proton Transport of a Polysulfone-Polyvinylpyrrolidone Membrane for Application in Vanadium Redox Flow Batteries - Wu, C.; Zhang, J.; Lu, S.; Xiang, Y.; Jiang, San Ping (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim An acid pretreatment strategy is developed to enhance the proton transport of polysulfone-polyvinylpyrrolidone (PSF-PVP) membranes for application in vanadium redox flow batteries (VRFB). The acid pretreatment leads to the formation of ionic conducting clusters with a size of around d=15.41 nm in the membrane (p-PSF-PVP). As a result, the proton conductivity and proton/vanadium ion selectivity of the p-PSF-PVP membrane increases to 6.60×10-2 S cm-1 and 10.63×107 S min cm-3, respectively, values significantly higher than 2.30×10-2 S cm-1 and 6.67×107 S min cm-3 of the pristine PSF-PVP membrane. Moreover, a VRFB assembled with the p-PSF-PVP membrane exhibits a high coulombic efficiency of 98.6 % and an outstanding energy efficiency of 88.5 %. The results indicate that treatment with either sulfuric acid or phosphoric acid leads to an improvement of membrane properties, and the acid pretreatment is a promising strategy to significantly enhance the performance of the PSF-PVP membrane for VRFB application.